Recent advances in coacervate protocells from passive catalysts to chemically programmable systems - Chen, Chong; Li, Jianwei (Springer Science and Business Media LLC, 2026)
This review highlights a clear change in focus in the study of coacervate droplets as protocell models, moving from their role as passive microreactors that concentrate reactants to their function as chemically programmable matter capable of information processing and lifelike behaviors. We use “Input → Written State → Output” as a guiding workflow, and discuss recent advances through three operational pillars. The first is local reactivity control, where the droplet microenvironment directs reaction pathways and spatial enzyme organization, including feedback loops where reactions regulate the physical state. The second pillar is the writing of internal states, which treats droplets as stimuli-addressable chemical memory with targets of selectivity, latency, and erasability. The third pillar involves external readouts, which transduce internal states into programmed cargo release and chemical signaling within environments and across protocell communities. Finally, we outline future perspectives, discussing the transition from programming deterministic functions to directing the evolution of protocell populations that exhibit collective behaviors. By offering a cohesive conceptual toolkit, this review provides new insights beyond the simple notion of “faster reactions in droplets” and toward the engineering of higher-order, cooperative architectures with lifelike functions.